Tratamiento de la Nic 16 propiedad planta y equipo de la empresa PROENERGY S.A en la ciudad de Babahoyo - Alcivar Arias, Cristina Julexy (2020)
This case study, TREATMENT OF IAS 16 PROPERTY, PLANT AND EQUIPMENT IS CARRIED OUT AT THE COMPANY PROENERGY SA LOCATED IN THE CITY OF BABAHOYO, this is a company oriented to provide solutions in the medium and low voltage electrical area offering their services and selling to large and small companies, public and private entities. Its activities range from the installation of meters in residences to the establishment of transformers complying with the technical specifications given by CNEL. It is addressed to the various provinces of Ecuador, including: Manabí, Los Ríos, Guayas. The company is located in the city of Babahoyo, whose address is Calle Juan Angoleto and Avenida 10, diagonal to the IESS Hospital parking lot. Focusing on the development of the PLANT PROPERTY AND EQUIPMENT we can say that they are those goods that belong to the company whose function is not to participate in the company's business activities, rather it is a permanent support in the production processes, these fixed assets must comply with certain characteristics to be considered as such, of which we can highlight the following, they are property of the company and are directly related to the activity carried out by the company, due to the various activities or production processes companies have reached the need to classify your fixed assets to streamline processes. It is also described that the norm indicates that the valuation criterion to be used is cost, making a distinction depending on whether it is the time of its incorporation, or moments after it. It also deals with the allocation of post-acquisition expenses as the book value of the asset. When developing this case study, it was obtained that the fixed assets within the companies dedicated to the provision of services represent an important item, therefore, their valuation is necessary. It was learned through an interview that the company considers as fixed assets everything that is part of the commercial activity such as machinery, vehicles, computer equipment, furniture and fixtures. It was verified that the company PROENERGY SA was not applying the adequate accounting treatment according to IAS 16, therefore, it was carrying the values of its accounting records in an inadequate way because the corresponding revaluation values of assets were not obtained, causing the values They presented were only the acquisition costs plus VAT. When applying the respective calculations and treatments to each depreciable and revalued asset, the difference in the values was seen immediately since their acquisition costs were already historical values and their values were updated to which the respective adjustment was obtained, giving the notable application of IAS 16.